The perspectives for genetically modified cellulosic ethanol in the Czech Republic - Pavla Blahova; Karel Janda; Ladislav Kristoufek (Charles University in Prague, Institute of Economic Studies (IES), 2014)
This paper connects the biofuels literature with genetic modifications literature by considering the potential of genetic modifications for increasing the efficiency of cellulosic biofuels production. This is done for one particular case through analyzing the effect of genetically modified corn adoption on overall yields of corn for silage. Our econometric model confirms that the use of genetically modified corn with inserted MON810 gene increases the overall corn biomass yield in the production and environmental conditions of the Central Europe, in particular in the Czech Republic.
Keywords: C23; Q16; Q42; 330; Cellulosic Biofuels; Genetic Modifications